When Do Firms Adjust Bonus Targets Intrayear? Evidence from Sales Executives' Targets* - Arnold, Markus; Artz, Martin; Grasser, Robert A. (Contemporary Accounting Research, 2023)
ABSTRACT This study investigates when and why intrayear bonus target revisions occur. This is important as intrayear target revisions occur regularly in practice but are not well understood. Specifically, we analyze two potential drivers of intrayear bonus target revisions: reduced managerial incentives owing to managers dropping out of the incentive zone of their piecewise defined bonus function and potential spillovers from planning target revisions that reflect changes in performance expectations during the year. We also investigate the effects of organizational characteristics on intrayear bonus target revisions. Using data collected from sales executives via multiple waves of surveys, we find evidence for both predicted drivers. In addition, consistent with our predictions, we find that the levels of delegated decision authority, intrafirm interdependencies, and information asymmetry negatively moderate the positive association between reduced managerial incentives and revision likelihood. Our paper contributes to the target setting literature by being the first study to investigate intrayear bonus target revisions and shed light on when firms commit to not revising such targets intrayear.